PENGARUH JENIS PELARUT TERHADAP RENDEMEN DAN KUALITAS MINYAK BEKATUL YANG BERASAL DARI BEKATUL BERAS (Oryza sativa L.) - Erlita Verdia Mutiara; A.A. Hesti Wulan S (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2013)
Indonesia is an agricultural country with the paddy crop as main product. The process of paddy hulling rice will yield the main product, bekatul rice and lock up as the side product. The use of bekatul rice has not been optimum in Indonesia, as it is only used as the feed for livestock and poultry. Bekatul rice has the potency as the oil source which is much used in of pharmacy and food industry as salad oil, raw material for cosmetics, health supplement. Bekatul oil contains 80 % fatty acid (oleat acid and linoleat acid). The research has the target to know the difference of n-hexane solvent, ether petroleum and chloroform against the rendemen and the quality of bekatul rice oil, and to know the type of solvent which yields rendemen and the best quality of bekatul rice oil. Bekatul rice oil was made by way of soxhletacy with n-heksan solvent, ether petroleum, and chloroform; the filtrate obtained was evaporated to obtain rough bekatul rice oil. The rough bekatul rice oil was purified by gum removing process ( de-gumming) and wax separation. The bekatul rice oil obtained was measured to know the rendemen and the quality of bekatul rice oil, quality test of bekatul rice oil included the physical test of pH and bias index as well as chemical test that indicated peroxide number test and acid number test. The result of the rendemen and the bekatul rice quality (afractive index, peroxide number and acid number) showed a significant difference on the n-hexane solvent which produced rendemen and the best quality of bekatul rice oil. Based on the research, it can be concluaded that the difference in the type of solvent can influence the rendemen and the quality of bekatul rice oil on n-hexane solvent witch produced rendemen and the best quality of bekatul rice oil.